1998
DOI: 10.1002/(sici)1099-0844(1998120)16:4<253::aid-cbf795>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fat on lymphocyte proliferation and metabolism

Abstract: The effect of diets enriched with fat containing different fatty acids on glucose and glutamine metabolism of mesenteric lymph nodes lymphocytes, spleen, and thymus and lymphocyte proliferation was examined. The following fat-rich diets were tested: (1) standard chow (CC); (2) medium chain saturated fatty acids (MS)--coconut fat oil; (3) long chain saturated fatty acids (LS)--cocoa butter; (4) monounsaturated fatty acids (MU)--canola oil (n-9); (5) polyunsaturated fatty acids (PU)--soybean oil (n-6). Of the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
2
14
0
1
Order By: Relevance
“…Oxidative stress and lipid peroxidation have been associated with impaired immune function and with the development of several diseases [52,53]. DHA presented a stimulating effect on expression of three genes related to defense and repair: growth arrest and DNA-damage-inducible protein (GADD45), glutathione reductase, and glutathione Stransferase A1 (GSTA1).…”
Section: Discussionsupporting
confidence: 88%
“…Oxidative stress and lipid peroxidation have been associated with impaired immune function and with the development of several diseases [52,53]. DHA presented a stimulating effect on expression of three genes related to defense and repair: growth arrest and DNA-damage-inducible protein (GADD45), glutathione reductase, and glutathione Stransferase A1 (GSTA1).…”
Section: Discussionsupporting
confidence: 88%
“…In vitro and in vivo studies have shown that fatty acids modulate a number of leukocyte functions (Arrington et al, 2001;Kelley, 2001), including proliferation (Otton et al, 1998;Granato et al, 2000;Furukawa et al, 2002;Cavaglieri et al, 2003), activation by antigens (Granato et al, 2000), natural killer cell activity (Yaqoob et al, 1998), cytokine release (Granato et al, 2000;Furukawa et al, 2002;Hara et al, 2003;Kurita-Ochiai et al, 2004), adhesion molecule expression (Yaqoob et al, 1998;Kurita-Ochiai et al, 2004), mitogenic signalling cascade activity (Yusufi et al, 2003), and cell death (Emenaker et al, 2001;Garnacho-Montero et al, 2002;Lima et al, 2002;Pompeia et al, 2002;Healy et al, 2003;Switzer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The cells were then collected, washed with PBS and used for enzymatic activity assays and/or measurements of glucose and glutamine oxidation. The cells obtained from rats or culture plates were disrupted through sonication (Vibra Cell, Manchester, CT, USA) as previously described (Otton et al 1998).…”
Section: Cell Culturementioning
confidence: 99%
“…4·1·3·7) and phosphate-dependent glutaminase (E.C. 4·1·3·7) were determined as described in our previous studies (Cooney et al 1986, Newsholme et al 1986, Pereira et al 1994, Otton et al 1998 and in other studies (Mansour 1963).…”
Section: Assay Of Enzyme Activitiesmentioning
confidence: 99%